Measuring the Mechanical Response of Sand-Rubber Composites as a Geotechnical Material - Amiralian, Saeid (Curtin University, 2017)
This thesis presents a comprehensive experimental program were conducted on 18 sand composites contain the various dosage of cementitious material and rubber buffing. According to the result, the structure of the composite matrix is defined by the percentage of rubber in the mixture, was directly affected by the geotechnical properties of composites. The stress-dilation correlation proposed from scale effect study was subsequently verified by creating a numerical model for predicting the shear strength behaviour of composites.